Ethnic-related diversity engagement differences in intercultural sensitivity among Malaysian undergraduate students - Tamam, Ezhar; Krauss, Steven Eric (Routledge, 2017)
This survey examines the association of ethnic-related diversity engagement with three interrelated dimensions of intercultural sensitivity among students in a public university with a multi-ethnic, multi-religious student population. A total of 447 respondents provided the data for analysis. Using multivariate analysis of variance (MANOVA), the findings suggest that the level of intercultural sensitivity among students is positively associated with students' level of ethnic-related diversity engagement, and that ethnic-related diversity engagement relates differentially to interaction attentiveness, interaction openness and interaction confidence dimensions of intercultural sensitivity. In summary, the findings add to the literature by clarifying the strength of the relationship of ethnic-related diversity engagement and dimensions of intercultural sensitivity. Implications of the findings are discussed.